The Effect of Dividend Policy, Financial Performance and Environmental Performance on Investor Reactions - Raden Bambang Budhijana (Syntax Corporation Indonesia, 2022)
Investors pay attention to the future business prospects of the investments they choose, although in investing the conditions of the investments they choose cannot be known with certainty. Investor's reaction is the response of the investor itself to the information provided by the company and can be positive or negative. The purpose of this study was to examine the effect of Dividend Policy, Financial Performance and Environmental Performance on Investor Reaction in manufacturing companies listed on the Indonesia Stock Exchange for the 2017-2021 Period and rarely discussed investor reaction. The method used in this research is to use panel data regression processing. The Findings of the analysis after going through the Chow test and the Haussman test show that the coefficient factors namely the Dividend Policy (, Financial Performance () and Environmental Performance ( have a significant influence on the Investor Reaction in the manufacturing company group. This research discussing more intense to the effect of Dividend Policy, Financial Performance and Environmental Performance on Investor Reaction in 24 companies listed on the Indonesia Stock Exchange (IDX) and participating in the PROPER program implementation for 5 years. The following conclusions were obtained: Dividend Policy, Financial Performance, Environmental Performance included in this research model have a positive effect on Investor Reactions proxied with Abnormal Returns. Managerial implication that can be made into future policies are regulations requiring companies to be more active in expressing environmental responsibility.